A TWO-DIMENSIONAL THERMODYNAMIC MODEL TO PREDICT HEART THERMAL RESPONSE DURING OPEN CHEST PROCEDURES - Dias, F. G.; Vargas, J. V. C.; Brioschi, M. L. (Revista de Engenharia Térmica, 2016)
In this work, the temperature distribution of the heart in an open chest surgery scenario is studied. It is also evaluated the cardiac thermal effects of the injection of a cooling liquid in the aorta root, which is used in infrared thermography. The finite element method was used to develop a model that predicts the temperature distribution modification in a 2-dimensional slice of the heart. This thermodynamic model allows the computational simulation of the thermal cardiac response to open chest procedures, which are required by cardiac surgery. The influence of several operating parameters (e.g., coronary flow rate, temperature) on the resulting thermal distribution is analyzed. Therefore, this analysis allows the identification of parameters that could be controlled to minimize the loss of energy, and consequently, avoiding the hazardous thermal distribution that could put the heart in danger during cardiac surgery.